Cardiorespiratory Fitness and Insulin Sensitivity in Overweight or Obese Subjects May Be Linked Through Intrahepatic Lipid Content - Haufe, Sven; Engeli, Stefan; Budziarek, Petra; Utz, Wolfgang; Schulz-Menger, Jeanette; Hermsdorf, Mario; Wiesner, Susanne; Otto, Christoph; Haas, Verena; de Greiff, Armin; Luft, Friedrich C.; Boschmann, Michael; et al. (Diabetes (New York, N.Y.), 2010)
Low cardiorespiratory fitness (CRF) predisposes one to cardiovascular disease and type 2 diabetes in part independently of body weight. Given the close relationship between intrahepatic lipid content (IHL) and insulin sensitivity, we hypothesized that the direct relationship between fitness and insulin sensitivity may be explained by IHL. We included 138 overweight to obese, otherwise healthy subjects (aged 43.6 +/- 8.9 years, BMI 33.8 +/- 4 kg/m(2)). Body composition was estimated by bioimpedance analyses. Abdominal fat distribution, intramyocellular, and IHL were assessed by magnetic resonance spectroscopy and tomography. Incremental exercise testing was performed to estimate an individual's CRF. Insulin sensitivity was determined during an oral glucose tolerance test. For all subjects, CRF was related to insulin sensitivity (r = 0.32, P < 0.05), IHL (r = -0.27, P < 0.05), and visceral (r = -0.25, P < 0.05) and total fat mass (r = -0.32, P < 0.05), but not to intramyocellular lipids (r = -0.08, NS). Insulin sensitivity correlated significantly with all fat depots. In multivariate regression analyses, independent predictors of insulin sensitivity were IHL, visceral fat, and fitness (r(2) = -0.43, P < 0.01, r(2) = -0.34, and r(2) = 0.29, P < 0.05, respectively). However, the positive correlation between fitness and insulin sensitivity was abolished after adjustment for IHL (r = 0.16, NS), whereas it remained significant when adjusted for visceral or total body fat. Further, when subjects were grouped into high versus low IHL, insulin sensitivity was higher in those subjects with low IHL, irrespective of fitness levels. Our study suggests that the positive effect of increased CRF on insulin sensitivity in overweight to obese subjects may be mediated indirectly through IHL reduction.